Polynomial systems theory applied to the analysis and design of multidimensional systems - Hätönen, Jari; Ylinen, Raimo (Zielona Góra: Uniwersytet Zielonogórski)
The use of a principal ideal domain structure for the analysis and design of multidimensional systems is discussed.
Keywords: nD systems; module of fractions; partial differential equations; polynomial systems theory